ANALISIS EFISIENSI BIAYA PRODUKSI MIE PADA UD MIE UJANG KABUPATEN JEMBER - Nadia Isnaini; Sri Kantun; Dwi Herlindawati (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
This study aims to measure the level of efficiency of raw noodle production costs at UD Mie Ujang, Jember Regency with standard costs as a reference in the use of production costs. This research belongs to the type of quantitative descriptive research. The type of data used is the main data in the form of production cost report documents of UD Mie Ujang, Jember Regency for the first quarter of 2022 and supporting data in the form of interview results related to the condition of production cost reports. The research informants are the owners and employees of UD Mie Ujang, Jember Regency. The results showed that the use of raw noodle production costs at UD Mie Ujang, Jember Regency in the first quarter of 2022 showed efficient results. The use of production costs is more efficient in producing super raw noodles compared to ordinary raw noodles. The results of cost efficiency can be used as a consideration and decision in determining the selling price of the next product.